Cardiovascular safety of mirabegron add‐on therapy to tamsulosin for the treatment of overactive bladder in men with lower urinary tract symptoms: A post hoc analysis from the MATCH study. Issue 1 (25th September 2020) - Katoh, Takao; Kakizaki, Hidehiro; Lee, Kyu‐Sung; Ishida, Kota; Katou, Daisuke; Yamamoto, Osamu; Jong, Jar Jar; Sumarsono, Budiwan; Uno, Satoshi; Yamaguchi, Osamu
Abstract: Objectives: To investigate the cardiovascular safety of mirabegron add‐on treatment to tamsulosin in male patients with residual overactive bladder symptoms. Methods: This was a post hoc analysis of MATCH, the first double‐blind, placebo‐controlled study comparing mirabegron and placebo as add‐on therapy to tamsulosin for treatment of overactive bladder in men with lower urinary tract symptoms. The analysis focused on treatment‐emergent adverse events relating to the cardiovascular system or blood pressure, and changes in vital signs during 12 weeks of follow‐up. Results: Cardiovascular‐related treatment‐emergent adverse events were reported by 6/566 patients, although only one serious treatment‐emergent adverse event was related to treatment (unstable angina in the tamsulosin + placebo group). Hypertension (two patients) and increased blood pressure (one patient) were reported in the tamsulosin + placebo group, but there were no blood pressure‐related treatment‐emergent adverse events among tamsulosin + mirabegron patients. There were no clinically meaningful changes from baseline in blood pressure, and changes in pulse rate were small (+1.2 bpm in the tamsulosin + mirabegron group). Increased pulse rate was more frequent with tamsulosin + mirabegron than with tamsulosin + placebo in older patients, although within the normal range. Conclusions: Cardiovascular‐related adverse events were uncommon in both treatment groups. Mirabegron is a well‐tolerated add‐on therapy to tamsulosin in Japanese and Korean males with residual overactive bladder symptoms.